2008
DOI: 10.1007/978-3-540-89439-1_41
|View full text |Cite
|
Sign up to set email alerts
|

Decidable and Undecidable Fragments of Halpern and Shoham’s Interval Temporal Logic: Towards a Complete Classification

Abstract: Abstract. Interval temporal logics are based on temporal structures where time intervals, rather than time instants, are the primitive ontological entities. They employ modal operators corresponding to various relations between intervals, known as Allen's relations. Technically, validity in interval temporal logics translates to dyadic second-order logic, thus explaining their complex computational behavior. The full modal logic of Allen's relations, called HS, has been proved to be undecidable by Halpern and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3
1

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 19 publications
(54 reference statements)
2
34
0
Order By: Relevance
“…Decidability of temporal neighbourhood logics over various classes of linear orders can be proved by reducing their satisfiability problems to that of the two-variable fragment of first-order logic over the same classes of linear orders [6]. In fact, neighbourhood temporal logic turns out to be a maximal decidable fragment of HS, when interpreted over any class of linear orders that contains at least one linear order with an infinitely ascending/descending sequence [4], [7], [8]. In this paper, we focus on interval logics of subinterval and super-interval structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decidability of temporal neighbourhood logics over various classes of linear orders can be proved by reducing their satisfiability problems to that of the two-variable fragment of first-order logic over the same classes of linear orders [6]. In fact, neighbourhood temporal logic turns out to be a maximal decidable fragment of HS, when interpreted over any class of linear orders that contains at least one linear order with an infinitely ascending/descending sequence [4], [7], [8]. In this paper, we focus on interval logics of subinterval and super-interval structures.…”
Section: Introductionmentioning
confidence: 99%
“…It can easily be shown that the proposed techniques cannot be directly lifted to the strict and proper cases. Moreover, the undecidability of various extensions of the logics of sub-interval and superinterval structures has been recently proved [4], [7], [12].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, F must contain at least one modality in the set { E , E }. This prevents modalities B and B to be included in F , as they would immediately yield undecidability [42] in the finite case. Then, it follows that F can contain only modalities from the set { A , A , E , E , L , L }, and thus it must belong to the diagram, which is a contradiction.…”
Section: Expressive Powermentioning
confidence: 99%
“…An optimal (NEXPTIME) tableau-based decision procedure for AĀ over the integers has been given in [5] and later extended to the classes of all (resp., dense, discrete) linear orders [6], while a decidable metric extension of the future fragment of AĀ over the natural numbers has been proposed in [7] and later extended to the full logic [4]. Finally, a number of undecidable extensions of AĀ have been given in [2,3].…”
Section: Introductionmentioning
confidence: 99%